PENGARUH DISIPLIN BELAJAR DAN LINGKUNGAN KELUARGA TERHADAP PRESTASI BELAJAR EKONOMI MATERI POKOK PERTUMBUHAN EKONOMIDI KELAS XI IPS SMA NEGERI 5 PADANGSIDIMPUAN - Erlina Sari Harahap (Institut Pendidikan Tapanuli Selatan, 2018)
This study to see the effect of Discipline Learning and Learning Achievement Against Family Environment Economy Topic Economic Growth Class XI IPS SMAN 5 Padangsidimpuan. Based on hypothesis testing found that F count = 16.357 compared with F table with significance level α = 0.05, obtained F table = 3.32. So it can be concluded that the F count> F table or 16.357> 3.32 then the hypothesis that the authors propose acceptable means discipline of learning and family environment jointly significant effect on the achievement of economic learning the subject matter of economic growth in Class XI IPS SMAN 5 Padangsidimpuan. That is the discipline of learning and family environment to be one of the driving variable in order to increase student achievement, especially against the subject matter of economics learning achievement of economic growth in Class XI IPS SMAN 5 Padangsidimpuan.